2018
DOI: 10.3906/vet-1704-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression levels in some candidate genes for mastitis resistance, milk yield,and milk quality of goats reared under different feeding systems

Abstract: This study aimed to identify the expression levels of some candidate genes for mastitis resistance (LTF and BRCA1), milk yield (POU1F1 and IGF-1), and milk quality (PPARγ and CSN2) in different feeding systems (pen-and pasture-based) used for Damascus goats. Milk samples were taken from all goats in both pen and pasture groups at 4 times, at the 1st, 3rd, 5th, and 7th months of the study. It was found that, compared to the pen group, the LTF and CSN2 genes in the pasture group had significant levels of upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In agreement with present finding, butterfat, protein, lactose and energy values were significantly tended to rise with advancing lactation as reported in West African dwarf goats (Charnobai et al, 1999), whereas Zeng et al (1997) reported high fat, protein, solids non-fat and total solids with the exception of lactose, in the first month after parturition, which declined slightly and then remained constant until drying-off in Alpine does. In accordance with the present study, daily milk production increased steadily for the first 4 weeks following parturition and then decreased gradually as reported by Zeng et al (1997), however, Yakan et al (2018) reported increased daily milk yield (g) from 1 st month to 3 rd month of lactation in Damascus goats.…”
Section: Results a N D Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with present finding, butterfat, protein, lactose and energy values were significantly tended to rise with advancing lactation as reported in West African dwarf goats (Charnobai et al, 1999), whereas Zeng et al (1997) reported high fat, protein, solids non-fat and total solids with the exception of lactose, in the first month after parturition, which declined slightly and then remained constant until drying-off in Alpine does. In accordance with the present study, daily milk production increased steadily for the first 4 weeks following parturition and then decreased gradually as reported by Zeng et al (1997), however, Yakan et al (2018) reported increased daily milk yield (g) from 1 st month to 3 rd month of lactation in Damascus goats.…”
Section: Results a N D Discussionsupporting
confidence: 93%
“…SCC shows an upward trend with the progression of the productive period resulting in a significant negative correlation between SCC and milk production (Gomes et al, 2006). Significantly higher SCC was reported by Zeng et al (1997) in Alpine does during the first 2 weeks of lactation (887 ± 400 X 10 3 /ml) and Damascus goats from 1 st month (488.04 ± 107.86) to 3 rd month (730.08 ± 189.23 ×1000/ml) as reported by Yakan et al (2018).…”
Section: Results a N D Discussionmentioning
confidence: 83%
“…: Product Length; FASN: Fatty Acids Synthase; SCD: Stearoyl-CoA Desaturase; ACACA: Acetyl-CoA Carboxylase Alpha; COX-2: Cyclooxygenase-2; TLR2: Toll-like Receptor 2; NF-kB: Nuclear factor Kappa B; LTF: Lactoferrin; PTX3: Pentraxin 3; NRF2: Nuclear Factor Erythroid 2-related Factor 2; ACTB: Actin-beta; G6PD: Glucose-6-phosphate Dehydrogenase. Genes Accession no Forward and reverse sequences of primers P.L Ref FASN NM_001285629.1 F: 5′-GCACACAATATGGACCCCCA-3′ R: 5′-CATGCTGTAGCCTACGAGGG-3′ 183 * SCD NM_001285619.1 F: 5′-ATCGCCCTTACGACAAGACC-3′ R: 5′-CATAAGCCAGACCGATGGCA-3′ 186 * ACACA XM_018064168.1 F: 5′-GCCTGCCCGAGTTTTGAGTG-3′ R: 5′-CGCACTCTGGAGCGGATAAA-3′ 105 * COX-2 XM_018060731.1 F: 5′-GTAGGCCAGGAGGTCTTTGG-3′ R: 5′- GCCTGCTTGTCTGGAACAAC-3′ 142 * NRF2 NM_001314327.1 F: 5′-CTGTTCTCTGCTGTCAAGGG-3’ R: 5′-AACTCGCCGGTCTCTTCATC-3’ 222 * TLR2 NM_001285603.1 F: 5′-TGCTGTGCCCTCTTCCTGTT-3′ R: 5′-GGGACGAAGTCTCGCTTATGAA-3′ 260 47 NF-kB XM_018049265.1 F: 5′-TGGGGATACTGAACAACGCC-3′ R: 5′-ATCTGTCTCAGGGCCTCCAT-3′ 115 * LTF NM_001285548.1 F: 5′-CAAGTGTGTGCCCAACTCTA-3′ R: 5′-GCTCTCTCCATTCGTGTTCTC-3′ 105 19 PTX3 XM_018048475.1 …”
Section: Methodsmentioning
confidence: 99%
“…Unlike GECs, SCs are easily extracted from milk samples in forms of pellets. They were also effectively utilized to assess the expression of some milk performance-related genes and proteins in buffalo and goat [ 14 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%